Pengaruh Profitabilitas, Likuiditas Dan Struktur Modal Terhadap Nilai Perusahaan Pada Perusahaan Ritail Yang Terdaftar Di Bursa Efek Indonesia Periode 2018-2020 - Wahyuddin Wahyudin; Devi Tri Ahyuni (Jurnal Akuntansi dan Keuangan, 2022)
This study aims to examine the effect of profitability, liquidity and capitalstructure on firm value in retail sector companies listed on the Indonesianstock exchange for the 2018-2020 period. The sample in this study are retailcompanies listed on the Indonesia Stock Exchange. In sampling, the authoruses a purposive sampling technique, namely the sampling method usingcertain criteria. Data obtained from the publication of the Indonesia StockExchange. This study uses as many as 36 observations with multiple linearregression estimation. The results of the study found that the profitability andcapital structure variables had an effect on firm value, while the liquidityvariable had no effect on firm value.